Comparison of Indonesian and Norwegian Laws regarding Criminal Responsibility of perpetrators with Intellectual/Mental Disabilities - Via Dianti, Pingkan Okta; Andini, Maria Angela Putri; Windari, Rusmilawati; Da Silva, Eugenia Brandao (Universitas Negeri Surabaya, 2024)
The criminal responsibility of offenders with mental or intellectual disabilities varies significantly across legal systems, influencing policies within the criminal justice framework. In some jurisdictions, provisions exist allowing for the consideration of disabilities as grounds for exoneration or mitigation of punishment. The reform of Indonesia's Criminal Code in 2023, particularly Articles 38 and 39, addresses the issue of criminal responsibility for individuals with mental or intellectual disabilities. However, challenges arise when the concept of diminished criminal liability is tied more to the defendant's mental or intellectual condition rather than their culpability in the criminal act itself. This study aims to examine and compare these legal regulations and policies with those of Norway. Using a juridical-normative method with legislative and comparative approaches, the research seeks to elucidate the differences in how Indonesia and Norway handle the criminal responsibility of offenders with disabilities. By doing so, this paper aims to clarify the regulatory frameworks governing the exoneration and reduction of criminal liability for individuals with disabilities in Indonesia, ensuring that law enforcement practices align with the rights and considerations afforded to such individuals